Pengaruh Sales Growth, Likuiditas Dan Ukuran Perusahaan Terhadap Financial Distress - Lise Roswati Rochendi; Nuryaman Nuryaman (Owner : Riset dan Jurnal Akuntansi, 2022)
The company's goal other than making a profit is to be able to continue to grow and survive in the competition, but the emergence of internal threats such as financial difficulties can hinder the achievement of the company's goals. Therefore, management is required to perform optimally in the company's activities, especially financial in order to avoid financial distress. This study aims to determine the effect of sales growth, liquidity and firm size on financial distress. The population of this study are transportation companies listed on the Indonesia Stock Exchange for the 2016-2021 period. The sample selection using purposive sampling technique, the sample obtained is 16 companies with a 6 year observation period so that there are 96 research data. The type of data used in this research is quantitative data. The data collection method uses secondary data in the form of financial reports. The method used is descriptive and verification method using a quantitative approach. The data analysis technique used in this research is logistic regression analysis, coefficient of determination, partial significance test using Eviews version 9. The results show that sales growth has no effect on financial distress, liquidity has no effect on financial distress and the size of the company has a negative effect on financial distress.